The role of efflorescent salts associated with sulfide-rich mine wastes in the short-term cycling of arsenic: Insights from XRD, XAS, and µ-XRF studies - Nieva, Nancy Eugenia (2021)
The evaporation of As-rich leachates generated by the weathering of sulfide-rich mine wastes accumulated in abandoned tailing dams of the La Concordia mine, triggers the widespread precipitation of saline crusts and efflorescences. Because these salts are highly soluble, they may release high concentrations of arsenic after rainfall events. Thus, the goal of this work is to assess the solid speciation of As in these efflorescences, which may help to understand the short-term cycling of As in the site. The results reveal that As is present only as As(V), while its capacity to be retained in the salts highly depends on their mineralogical composition. Hydrous sulfates, such as gypsum and epsomite show a very low capacity to scavenge As, while copiapite retains the highest concentrations of this element. The spectroscopic evidences suggest that in this mineral, As(V) is included within the lattice, substituting sulfate in the tetrahedral sites. Because copiapite is highly soluble, it may be considered as one of the most important transient reservoirs of As in the site that can release high concentrations of this hazardous pollutant during the occasional rainfall events produced during the wet season.